SIKAP DALAM MEMEDIASI HUBUNGAN KESADARAN LINGKUNGAN DENGAN NIAT BELI PRODUK KOSMETIK RAMAH LINGKUNGAN - Nyoman Dara Paramita; Ni Nyoman Kerti Yasa (Jurnal Manajemen dan Kewirausahaan, 2015)
The purpose of this study was to determine the role attitudes to mediate the relationship between environmental awareness with the purchase intention eco-friendly cosmetics “The Body Shop” in Denpasar. Samples taken were 105 respondent, used purposive sampling techniques. This study used SEM analysis and the Sobel Test. The results showed that, the higher the environmental awareness tent to increase purchase intention of consumers to buy eco-friendly cosmetics brand “The Body Shop.” However, consumer attitudes did not affect the relationship between environmental awareness with the intention to buy eco-friendly cosmetic products. This suggested that eventhough without any positive consumer attitude. The higher environmental awareness could enhance the purchase intention towards eco-friendly cosmetic products “The Body Shop.”